Nitrogen stable isotopes composition in soil, plant leaves and response to seasonal changes along an urban-rural environmental gradient - Xiaoniu Xu; Bui Van Thang; Nguyen Van Quy; Manh Hung, Bui; Hong Hai, Nguyen; Van Cuong, Le; Vu Van Long; Fanhong Wang (Journal of Forestry Science and Technology, 2025)
Nitrogen stable isotopes (δ15N) abundance provides useful information on nitrogen input, transformation, and output, which indirectly reflect the characteristics of nitrogen cycling in terrestrial ecosystems. Here, our primary objectives were to: (i) examine how seasonal changes affect the δ15N values in various soil depths, as well as in tree leaves and (ii) compare differences among three forest sites (Shushan National Forest Park_DSS), Zipengshan National Forest Park_ZPS, and Wanfoshan National Forest Park_WFS) representing urban, suburban, and rural environmental conditions in Anhui Province, China. Soil and plant foliar samples were collected seasonally from Quercus acutissima Carruth. forests among the three sites from July 2017 to June 2018. The study results revealed that: (1) There was a significant difference in the δ15N values between the 0-10 cm and 10-20 cm soil depths in all three experimental sites. (2) The seasonal change trends of δ15N in DSS at 0–10 cm soil depth demonstrated that values were highest in fall 2017 and lowest in summer 2017, whereas values at ZPS and WFS sites were highest in summer 2017 and lowest in spring 2018. At 10-20 cm soil depth, DSS and ZPS had maximum δ15N values in Fall 2017 and lowest in summer 2018. (3) The δ15N values in both young and mature leaves were notably greater at the urban sites than those at the suburban and rural sites. The findings from this study revealed that seasonal and site variation significantly increased the Nitrogen stable isotope composition.